(untitled) (Texas Journal of Medical Science, 2023)
In anorectal anomalies, combined malformations of the urogenital system are often observed [1,5,7]. This can be explained by the close relationship between the embryonic development of these organs and systems. It is no coincidence that a lot of attention in the literature of the last decade is paid to urological problems of anorectal anomalies [ 12,15,20]. However, the true frequency has not yet been established and the structure of pathological conditions of urogenital system in anorectal anomalies has not been fully studied, the consequences of their delayed diagnosis have not been analyzed, treatment and tactical and operative technical aspects have not been developed and the organizational side of the issue needs improvement